2013
DOI: 10.1186/1752-1947-7-149
|View full text |Cite
|
Sign up to set email alerts
|

Primary hypothyroidism with growth failure and pituitary pseudotumor in a 13-year-old female: a case report

Abstract: IntroductionPrimary hypothyroidism is a well-known cause of poor linear growth in children. A rare finding with profound or long-standing disease is anterior pituitary enlargement (pituitary pseudotumor). This case highlights this uncommon finding, discusses clinical situations in which gradual dose escalation of levothyroxine may be advisable and reviews adjuvant therapies that have been previously attempted to improve final height in the setting of profound hypothyroidism.Case presentationWe report the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Conversely, the lack of negative feedback in the continuous reduction of thyroid hormone causes excessive secretion of TRH, and conduce to a proliferation of TSH secreting cells, which results in compensatory enlargement of the pituitary gland (10). Long-term primary hypothyroidism-induced pituitary hyperplasia has been confirmed by many studies (7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, the lack of negative feedback in the continuous reduction of thyroid hormone causes excessive secretion of TRH, and conduce to a proliferation of TSH secreting cells, which results in compensatory enlargement of the pituitary gland (10). Long-term primary hypothyroidism-induced pituitary hyperplasia has been confirmed by many studies (7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 98%
“…The full text was read, and 18 studies that met the inclusion criteria were selected for the final literature review. We reviewed 18 case reports of children or adolescents with short stature or hypogonadotropic hypogonadism from 2001 to 2019 (Table 4) (7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Of these, 17 studies reported delayed bone age and growth retardation (7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)25), but only 6 studies measured GH, with 5 studies reporting a decrease in GH (10,12,18,19,25).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The HSDS increased rapidly during the first year, but then HSDS slowly progressed during the next half year with rapid bone age progression. Case reports of prolonged primary hypothyroid girl with growth failure and delayed puberty showed incomplete recovery of growth potential with only thyroxine therapy 5 6) . The deficit in adult stature correlated with the duration of the hypothyroid state before treatment, so it is recommended to use a lower than usual replacement dosage of levothyroxine and/or to consider delaying puberty and epiphyseal fusion pharmacologically 1) .…”
Section: Discussionmentioning
confidence: 99%
“…The most common and prominent manifestation of chronic acquired hypothyroidism in children is profound growth failure, which is severe and progressive 4) . Thyroxine supplementation improves all the clinical signs and symptoms except for growth failure 5 6) . Accelerated growth often does not result in restoration of full growth potential, due to the rapid increase in skeletal age during the first 18 months of treatment 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies, mostly conducted in children, investigated the hormonal axes in patients affected by IIH, reporting isolated pituitary alterations such as GH deficiency (GHD) or central hypothyroidism (7)(8)(9). Full restoration of the pituitary function occurred upon treatment with acetazolamide or lumboperitoneal shunting (10,11).…”
Section: Introductionmentioning
confidence: 99%